An investigation on the creativity and aesthetic value of commercial photography in Malaysia : a case of advertising campaign on billboard / Md Nagib Padil - Padil, Md Nagib (2006)
Introduction: This research is an investigation on the creativity and aesthetics value of commercial photography in Malaysia of advertising campaign on billboard advertisement. Statements of problems: More images and campaigns on billboard advertisement in Malaysia have been exploited by the related parties in advertising production. Most of the images represented the Western culture and life, without considering the effects to the Malaysian surrounding and culture. Methodology: Applied research methods use quantitative and qualitative measurement. Interview and design survey to obtain information and feedback from the respondents and collection data from observation was made by recording sample on billboard advertisement. Finding: The findings of this research, is to find and apply the importance of creativity and artistic in photography as the main medium to promotion, information and education on billboard advertisement and to persuade the society to use the billboard as an important medium. Conclusion: The conclusion for this research is, on whole, it is agreed that effective creativity and aesthetic values must be emphasized in every images of commercial photography in Malaysia on future to attract the attention of society which can be as a main medium for information. Recommendation: The researcher offers the following recommends that the outline, rules and process in producing commercial photographic images on billboard advertisements must be investigate from the basic level. Terms of ideas, concept and contents must be unified into producing an image that can be used as a main medium for promotion, information and education to benefit the community.